2021
DOI: 10.1128/aac.00140-21
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Pharmacokinetics of High-Dose Oral versus Intravenous Rifampicin in Patients with Tuberculous Meningitis: a Randomized Controlled Trial

Abstract: Background Higher doses of intravenous rifampicin may improve outcomes in tuberculous meningitis but is impractical in high burden settings. We hypothesized that plasma rifampicin exposures would be similar between oral 35 mg/kg and intravenous 20 mg/kg, which has been proposed for efficacy trials in tuberculous meningitis. Materials and methods We performed a randomized parallel group pharmacokinetic study nested within a clinical trial of intensified antimicrobial therapy for tuberculous meningitis. HIV-posi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The study conducted by Wasserman and colleagues also had two intervention groups, which received either high-dose oral rifampin at 35 mg/kg/day or intravenously at 20 mg/kg/day. It had a low risk of performance and detection bias as the outcome measure was an objective PK endpoint; we found that lack of participant blinding could not have significantly affected the outcome (13). In summary, all the included studies had a low risk of selection, attribution, and other bias.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 86%
See 4 more Smart Citations
“…The study conducted by Wasserman and colleagues also had two intervention groups, which received either high-dose oral rifampin at 35 mg/kg/day or intravenously at 20 mg/kg/day. It had a low risk of performance and detection bias as the outcome measure was an objective PK endpoint; we found that lack of participant blinding could not have significantly affected the outcome (13). In summary, all the included studies had a low risk of selection, attribution, and other bias.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 86%
“…In two studies the intensified regimen involved quinolones, one of them containing levofloxacin at 20 mg/kg/day (11), while another one included moxifloxacin at 400 mg/day or 800 mg/day (10). And in one study from Sean Wasserman, the intervention group treatment consisted of high-dose rifampin plus linezolid, as well as other first-line antituberculosis drugs, one intervention arm applied aspirin at the same time (13). For the method of rifampin concentration detection, in a study by Ruslami (10), rifampin concentration was analyzed by validating high performance liquid chromatography assays (HPLC).…”
Section: Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations